Ocena stanja ohranjenosti habitatnega tipa 91E0* Obrečna vrbovja, jelševja in jesenovja v območju Natura 2000 Ličenca pri Poljčanah - Alagić, Ajša (Gozdarski vestnik, 2021)
The conservation status of the habitat type 91E0* Alluvial forests with Alnus glutinosa and Fraxinus excelsior (Alno- -Padion, Alnion incanae, Salicion albae) is rather alarming in Slovenia. In Slovenia, its status has been assessed as bad and the trend as negative which implies an additional possibility of deterioration. The above-mentioned forest habitat is the priority or preferential habitat type for which a special EU care is foreseen. Due to its small size and fragmentation, it is often overlooked and inappropriately treated. In order to improve its recognizability and get to know its characteristics in the field, we gave it a special attention in the framework of the LIFE Integrated Project for Enhanced Management of Natura 2000 in Slovenia. In our research, we studied the status of the habitat type 91E0* in Natura 2000 area Ličenca pri Poljčanah in detail by using the field mapping method. In this manner, we determined the area of stands of this habitat type and compared it with the existing habitat type 91E0* zones. We were detecting the occurrence of key tree species or, respectively, tree composition of stands, their regeneration and kinds of pressures and threats for the 91E0* habitat type in this area. Among the various known sub-types of the habitat type 91E0*, we found primarily the black alder (Alnus glutinosa) forest subtype, but also fragments of the subtype with willows and poplar. In some places, smaller stands of willows (Salix spp.) and narrow-leafed ash (Fraxinus angustifolia) were also found in the forest. We discovered that the habitat type 91E0* area in the Natura 2000 Ličenca pri Poljčanah actually occupies only around a fourth of the existing habitat type zones area. The analysis of the tree composition showed mainly the ingrowth of spruce in the black alder forests, which is not naturally present in this habitat type. We discovered that the regeneration of the black alder is very reduced in the studied area. The decline of the black alder stands is additionally influenced by diverse pressures and threats, e. g. the vicinity of the agricultural lands, waste, fragmentation of black alder stands, spreading of the non-native invasive plants, water regulations, vicinity of the traffic roads, sites drainage, etc. Consequently, the conservation status of the stands of this habitat type has been in most cases evaluated as unfavorable to bad. In order to improve the status of the riparian forests in the Ličenca pri Poljčanah area we also presented suggestions for concrete conservation measures.
Keywords: alluvial forests; Alnus glutinosa; black alder forests; conservation status; črnojelševje; field mapping; habitat type; habitatni tip; Natura 2000; obrečni gozdovi; stanje ohranjenosti; terensko kartiranje